2023
DOI: 10.1101/2023.07.07.548164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial vampirism mediated through taxis to serum

Siena J. Glenn,
Zealon Gentry-Lear,
Michael Shavlik
et al.

Abstract: Severe bacterial infections of the gastrointestinal (GI) tract instigate GI hemorrhaging that can lead to bacteremia, sepsis, and death. Pathogens preferentially colonize sites of injury, delaying healing and exacerbating tissue damage, but the underlying mechanisms are not well understood. We find that Enterobacteriaceae species are remarkably sensitive to human serum and perceive femtoliter quantities as a potent attractant. This behavior is driven by chemotaxis and the Tsr chemoreceptor, which recognizes L-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 98 publications
(260 reference statements)
0
14
0
Order By: Relevance
“…3H), and found that the tsr mutant is unable to respond to either effector. Since our earlier work demonstrated that the tsr strain retains chemotaxis to other stimuli 9 we conclude that Tsr is responsible for indole chemorepulsion.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…3H), and found that the tsr mutant is unable to respond to either effector. Since our earlier work demonstrated that the tsr strain retains chemotaxis to other stimuli 9 we conclude that Tsr is responsible for indole chemorepulsion.…”
Section: Resultsmentioning
confidence: 54%
“…In this assay, a constant flow of approximately 300 femtoliters per minute is applied to inject the effector through a glass microcapillary 0.5 µm in diameter; chemoattraction is observed as an influx of cells into the field of view over time and congregation near the source, and chemorepulsion is observed as decreasing cells over time and avoidance of the central effector source (Fig. 1C-E) 9 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations